Pengaturan Zona Nilai Tanah sebagai Dasar Penilaian Tanah oleh Badan Pertanahan Nasional - Narindra, Hawin; Permadi, Iwan; Sudarsono, Sudarsono (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study discussed the arrangement of the land value zone as the basis for a fair land valuation by the National Land Agency. The National Land Agency as an extension of the non-departmental government had the authority to regulate and carry out the allotment of land. This study used a normative juridical approach to address the legal problems encountered. The method used legislation and conceptual approaches. The results showed that the land value zone could be used as a basis for a fair land valuation by the National Land Agency. However, at present, there were no specific legal regulations governing land value zones which result in a vacuum and legal uncertainty so that regulations were needed that govern the operation of Land Value Zones. Legislation that was considered ideal was a ministerial regulation made by the Ministry of Agriculture and Spatial Planning/National Land Agency.